Audit committee attributes and audit quality: A benchmark analysis - Osariemen Asiriuwa; Edosa Joshua Aronmwan; Uwalomwa Uwuigbe; Olubukola Ranti Uwuigbe (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
This study examined audit committee attributes and audit quality with emphasis on the specific requirements of the 2011 SEC code. The study applied the deductive approach via the expost facto research design and the Binary probit regression model in analyzing the various hypotheses put forward in study. Data used for the study were gathered for 150 firm-year observations from the annual reports of quoted companies on the floor of the Nigerian Stock Exchange. Findings from the study revealed that audit committee size, frequency of meetings, number of expertise and overall effectiveness all have a positive relationship with audit quality. However, only size and overall effectiveness was significant in their relationship. The study recommends that since the significant positive nature of audit committee effectiveness show that four attributes jointly account for effectiveness, firms are encouraged to establish audit committees that have all these attributes. Furthermore, the requirement of having a 6-member audit committee is sound and empirically proven to aid audit quality. Therefore, firms yet to subscribe to these should hasten up, while sanctions should be made for firms that do not.
Keywords: M41; G21; 650; audit committee attributes; audit quality; audit committee effectiveness; audit committee size; frequency of meetings